2020
DOI: 10.1093/ecco-jcc/jjz203.026
|View full text |Cite
|
Sign up to set email alerts
|

OP27 Long-term safety and efficacy of risankizumab treatment in patients with Crohn’s disease: Final results from the Phase 2 open-label extension study

Abstract: Background Efficacy and safety of the IL-23 inhibitor risankizumab (RZB) have been assessed in patients with moderate-to-severe Crohn’s disease (CD) following induction/maintenance treatment.1,2 Responders to RZB in a Phase 2 induction/maintenance study2,3 could enrol in an open-label extension (OLE), NCT02513459.4 Final safety and efficacy results from this RZB OLE study are reported here. Methods Patients achieving clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Nine percent of patients had serious infections while 5% of patients reported opportunistic infections. There were no malignancies or deaths (Ferrante et al, 2020).…”
Section: Risankizumabmentioning
confidence: 90%
See 1 more Smart Citation
“…Nine percent of patients had serious infections while 5% of patients reported opportunistic infections. There were no malignancies or deaths (Ferrante et al, 2020).…”
Section: Risankizumabmentioning
confidence: 90%
“…The long-term safety of risankizumab was studied in the phase 2 OLE study and no new safety signals were noted; 92% of patients reported AEs and 35% of patients experienced serious adverse events (Ferrante et al, 2020). The most common AEs included nasopharygnitis (31%), gastroenteritis (23%), and fatigue (20%) (Ferrante et al, 2020). Nine percent of patients had serious infections while 5% of patients reported opportunistic infections.…”
Section: Risankizumabmentioning
confidence: 99%
“…Risankizumab, an IL-23 inhibitor, has shown good treatment outcomes for CD [ 41 ]. The leukocyte migrating inhibitor sphingosine 1-phosphate (S1P) receptor modulator, ozanimod, is already used for UC treatment in the United States [ 42 ].…”
Section: Inflammatory Bowel Disease and Malignanciesmentioning
confidence: 99%
“…Risankizumab is a selective IL-23 inhibitor that is effective and safe in treating CD with significant rates of long-term clinical remission in both advanced therapy-naïve and multi-refractory patients in clinical trials and real-world experience data from the USA and Europe. [2][3][4][5][6][7] As the Middle Eastern region is often under-represented in registration trials for therapies in IBD, clinical efficacy and safety data for advanced therapies in this emerging cohort of patients with IBD is lacking. 8 Here, we present our early experience from a tertiary IBD centre in the United Arab Emirates of risankizumab persistence, efficacy and safety in an advanced therapy-naïve and exposed group of 15 patients with CD with a median follow-up of 52 weeks (IQR 43 weeks).…”
mentioning
confidence: 99%